SME Contributions to Employment, Job Creation, and Growth in the Arab World - Nasr, Sahar (World Bank, Washington, DC, 2014)
Recent economic and political developments have highlighted a challenge shared across the Arab region of generating employment, promoting inclusive growth, and improving competitiveness. In the short run, weakened macroeconomic fundamentals in the developing economies of the Middle East and North Africa are a key challenge. The region's main challenge is to achieve sustainable growth that delivers the quantity and quality of jobs needed. An inclusive and competitive private sector has proven to be one of the most effective and long-term solutions for this challenge. This paper provides an analytical framework to diagnose and identify key challenges to the growth of small and medium enterprises that is supported by a quantitative model based on the World Bank's Enterprise Surveys database. The findings reconfirm that the route to a sustained role for small and medium enterprises in job creation requires improving the credibility of reforms, the effectiveness of policies, and equitable enforcement. Although one size fits all is infeasible for Arab countries, it is important to design policies across sectors to create productive employment and promote economic growth. Supporting innovation and enhancing access to finance are central to the development agenda for small and medium enterprises. And creating an enabling environment and setting up accountable institutions are key to ensure equal opportunity and inclusive growth.